Richard Wright y el carne de biblioteca - Miller, William, 1959-; Christie, R. Gregory, 1971-; Vega, Eida de la. (New York : Lee and Low Books, 2003)
Based on a scene from Wright's autobiography, Black boy, in which the seventeen-year-old African-American borrows a white man's library card and devours every book as a ticket to freedom.
007-010.
Keywords: Wright, Richard, -- 1908-1960 -- Juvenile fiction; Wright, Richard, -- 1908-1960 -- Novela juvenil; African Americans -- Juvenile fiction; Afronorteamericanos -- Novela juvenil; Bibliotecas -- Novela juvenil